Contourlet based Brain Tumor Classification - Prakash.H.Patil, K.Manju (International Journal of Scientific Research and Management (IJSRM), 2016)
— In this paper we proposed a new method for Brain Tumor classification using Probabilistic neural network with contourlettransformation. The conventional methods like Computerized Tomography and Magnetic Resonance Images are based on humaninspection for tumor classification and detection. These methods are inefficient and are also non reproducible for large amount of data.Also, those methods includes noise due to operator performance which creates serious inaccuracies in tumor classification. NeuralNetworks shows good results in medical diagnosis which is combined here with contourlet transform . Decision making is based on twosteps (i) Image reduction and Feature extraction using contourlet transform (ii) Classification using probabilistic NeuralNetwork(PNN). Performance evaluation on various brain tumor images shows fast and better recognition rate and also lowcomputational requirements, when compared to pre vious classifiers.